The Athena trials: Autologous adipose‐derived regenerative cells for refractory chronic myocardial ischemia with left ventricular dysfunction. Issue 2 (23rd September 2016) - Henry, Timothy D.; Pepine, Carl J.; Lambert, Charles R.; Traverse, Jay H.; Schatz, Richard; Costa, Marco; Povsic, Thomas J.; David Anderson, R.; Willerson, James T.; Kesten, Steven; Perin, Emerson C.
Abstract : Objective: To assess safety and feasibility of autologous adipose‐derived regenerative cells (ADRCs), for treatment of chronic ischemic cardiomyopathy patients. Background: Preclinical and early clinical trials suggest ADRCs have excellent potential for ischemic conditions. Methods: The Athena program consisted of two parallel, prospective, randomized (2:1, active: placebo), double‐blind trials assessing intramyocardial (IM) ADRC delivery [40‐million, n = 28 (ATHENA) and 80‐million (ATHENA II) cells, n = 3]). Patients with an EF ≥20% but ≤45%, multivessel coronary artery disease (CAD) not amenable to revascularization, inducible ischemia, and symptoms of either angina (CCS II–IV) or heart failure (NYHA Class II–III) on maximal medical therapy were enrolled. All patients underwent fat harvest procedure (≤450 mL adipose), on‐site cell processing (Celution® System, Cytori Therapeutics), electromechanical mapping, and IM delivery of ADRCs or placebo. Results: Enrollment was terminated prematurely due to non‐ADRC‐related adverse events and subsequent prolonged enrollment time. Thirty‐one patients (17‐ADRCs, 14‐placebo) mean age 65 ± 8 years, baseline LVEF(%) 31.1 ± 8.7 (ADRC), 31.8 ± 7.7 (placebo) were enrolled. Change in V02 max favored ADRCs (+45.4 ± 222 vs. −9.5 ± 137 mL/min) but there was no difference in left ventricular function or volumes. At 12‐months, heart failure hospitalizations occurred in 2/17 (11.7%) [ADRC] and 3/14 (21.4%) [placebo]. Differences in NYHA and CCS classes favored ADRCs at 12‐months with significant improvement in MLHFQ (−21.6 + 13.9 vs. −5.5 + 23.8, P = 0.038). Conclusions: A small volume fat harvest, automated local processing, and IM delivery of autologous ADRCs is feasible with suggestion of benefit in "no option" CAD patients. Although the sample size is limited, the findings support feasibility and scalability for treatment of ischemic cardiomyopathy with ADRCs. © 2016 Wiley Periodicals, Inc.